2013
DOI: 10.4103/0972-0707.108208
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of five different herbal extracts as an antimicrobial endodontic irrigant using real time quantitative polymerase chain reaction

Abstract: Context:Sodium hypochlorite is the most commonly used irrigant but it has disadvantage like high cytotoxicity. So there is a need to find an alternative to 5.25% Sodium hypochlorite against microorganism Enterococcus faecalis and Candida albicans. Literature has shown that these 5 extracts namely Terminalia chebula, Myristica frangrans, Aloe barbadensis, Curcuma longa and Azadaricta indica has good properties which can be used as a potential endodontic irrigant.Aims:To evaluate the antimicrobial efficacy of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 18 publications
4
52
0
Order By: Relevance
“…28 BRETAS LP et al All groups presented antimicrobial activity against E. faecalis. This finding corroborates various studies 20,22,23,29 that have shown acceptable bactericide effects among various natural extracts and Ca(OH) 2 associated with CPMC and chlorhexidine against E. faecalis.…”
Section: Antimicrobial Activitysupporting
confidence: 80%
“…28 BRETAS LP et al All groups presented antimicrobial activity against E. faecalis. This finding corroborates various studies 20,22,23,29 that have shown acceptable bactericide effects among various natural extracts and Ca(OH) 2 associated with CPMC and chlorhexidine against E. faecalis.…”
Section: Antimicrobial Activitysupporting
confidence: 80%
“…A strong correlation has been observed between apical periodontitis and the presence of bacteria and fungi in canals; if they persist in the root canal system at the time of obturation, there is a higher risk of failure 1,10 . C. albicans is the second most common cause of recalcitrant infections after E. faecalis.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that NaOCl inhibited C. albicans completely and the neem extract had better efficacy than CHX. An in vitro evaluation of 5 different herbal extracts as endodontic irrigants against E. faecalis and C. albicans using quantitative polymerase chain reaction revealed that neem was highly efficient to 5.25% NaOCl in reducing the counts of these microorganisms within the root canals when compared with other extracts 10 . Bohora et al 11 compared the antibacterial efficacy of neem leaf extract and 2% NaOCl against E. faecalis, C. albicans and mixed culture, and found that neem leaf extract is a viable medicament against both microorganisms and even against mixed culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Many research works are being carried out to focus the treatment using herbal extracts. 8 In this series, the present study was conducted to evaluate the inhibitory effect of leaves of Garcinia imberti bourd towards the species of Candida isolated from root canal infection.…”
Section: Introductionmentioning
confidence: 99%